2006
DOI: 10.1016/j.molcel.2006.06.013
|View full text |Cite
|
Sign up to set email alerts
|

SCFβTrCP-Mediated Degradation of Claspin Regulates Recovery from the DNA Replication Checkpoint Response

Abstract: During replicative stress, Claspin mediates the phosphorylation and consequent activation of Chk1 by ATR. We found that during recovery from the DNA replication checkpoint response, Claspin is degraded in a betaTrCP-dependent manner. In vivo, Claspin is phosphorylated in a canonical DSGxxS degron sequence, which is typical of betaTrCP substrates. Phosphorylation of Claspin is mediated by Plk1 and is essential for binding to betaTrCP. In vitro ubiquitylation of Claspin requires betaTrCP, Plk1, and an intact DSG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
274
0
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 273 publications
(287 citation statements)
references
References 58 publications
(85 reference statements)
11
274
0
2
Order By: Relevance
“…Three papers published during the review of this manuscript have identified amino acids 29-34 of Claspin as a phosphorylation-dependent proteasomal degradation motif required for binding of the ubiquitin ligase SCF b-TrCP to Claspin. [22][23][24] However, mutation of Ser30 and Ser34, which has been shown to abolish SCF b-TrCP -mediated degradation of Claspin [22][23][24] did not increase the stability of a caspaseresistant Claspin construct in apoptotic cells. These data indicate that the stability of Claspin during apoptosis is regulated by a ubiquitin ligase and/or a degradation signal different from that responsible for its degradation during normal cell cycle progression and recovery from checkpoint arrest.…”
Section: Discussionmentioning
confidence: 94%
“…Three papers published during the review of this manuscript have identified amino acids 29-34 of Claspin as a phosphorylation-dependent proteasomal degradation motif required for binding of the ubiquitin ligase SCF b-TrCP to Claspin. [22][23][24] However, mutation of Ser30 and Ser34, which has been shown to abolish SCF b-TrCP -mediated degradation of Claspin [22][23][24] did not increase the stability of a caspaseresistant Claspin construct in apoptotic cells. These data indicate that the stability of Claspin during apoptosis is regulated by a ubiquitin ligase and/or a degradation signal different from that responsible for its degradation during normal cell cycle progression and recovery from checkpoint arrest.…”
Section: Discussionmentioning
confidence: 94%
“…Using reticulocyte lysates, we reconstituted the components of the SCF Fbxl17 and Sufu in an in vitro reaction, as previously done (Peschiaroli et al , 2006). We observed ubiquitylation of Sufu wild type (WT), while the Sufu K257R was ubiquitylated to a reduced extent (Fig EV2C).…”
Section: Resultsmentioning
confidence: 99%
“…If this point precedes the onset of mitosis in late G 2 , it is possible to predict a transition period during which Chk1 could no longer be activated in response to DNA damage but Chk2 would (Figure 8). In fact, there is evidence that Chk1 is refractory to ATR-mediated phosphorylation and activation by DNA damage in mitotic cells (Shiromizu et al, 2006), possibly owing to cell cycle phase-specific degradation of the adaptor protein Claspin (Mailand et al, 2006;Peschiaroli et al, 2006), therefore it is highly plausible that the transition precedes the onset of this phase. We hypothesize that during this transition period Chk2 becomes increasingly, and ultimately solely, responsible for G 2 delay in response to damage in cells which are imminently about to enter mitosis (Figure 8).…”
Section: Discussionmentioning
confidence: 99%